1990
DOI: 10.1002/1097-0355(199022)11:2<142::aid-imhj2280110206>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Early home intervention and socio-emotional development of preterm infants

Abstract: In the present study, the effects of developmental intervention and parent‐infant interaction intervention on the social competence and emotional development of preterm infants were assessed. The results suggest that early home intervention focused on the infant's development facilitates social competence and adaptation, whereas intervention focused on the parent‐infant interaction resulted in greater emotional security on the part of the infant. Social competence during the second year of life was predicted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Our principal for selecting this age group is that, by 7 months, preterm infants have had more ot 'than younger infants to "catch up full-term infants. They sustain a period oî ,, with their mothers, necessary UU..»B -.^ still-face procedure In addition, previous findings indicate that mother-infant interaction patterns consolidate and normalize over the first year (Frodi & Thompson, 1985); infants' still-face responses at 6 months predict security of attachment at 1 year (Cohn et al, 1991;Tronick et al, 1982), and social competence in 8-month-olds predicts social competence at 2 years (Barrera, Doucet, & Kitching, 1990). Thus, by 7 months, it might be possible to identify patterns of risk for later socialemotional disturbance.…”
Section: The Present Studymentioning
confidence: 99%
“…Our principal for selecting this age group is that, by 7 months, preterm infants have had more ot 'than younger infants to "catch up full-term infants. They sustain a period oî ,, with their mothers, necessary UU..»B -.^ still-face procedure In addition, previous findings indicate that mother-infant interaction patterns consolidate and normalize over the first year (Frodi & Thompson, 1985); infants' still-face responses at 6 months predict security of attachment at 1 year (Cohn et al, 1991;Tronick et al, 1982), and social competence in 8-month-olds predicts social competence at 2 years (Barrera, Doucet, & Kitching, 1990). Thus, by 7 months, it might be possible to identify patterns of risk for later socialemotional disturbance.…”
Section: The Present Studymentioning
confidence: 99%
“…Fifth, several studies demonstrated the positive effects of increasing parental sensitivity and responsivity to infant cues (Barrera et al 1990; Seifer et al 1991). Such parenting practices also have positive impact on the development of typical infants and toddlers.…”
Section: Introductionmentioning
confidence: 99%
“…With the survival rate improving, however, the focus has shifted to decreasing morbidity. Researchers have investigated interventions to enhance development, and most conclude that modeled interventions (demonstrated by a professional for the parent to demonstrate in return and use at home) are most effective (Barrera, Doucet, & Kitching, 1990;Barrera, Rosenbaum, & Cunningham, 1986;"Enhancing the Outcomes," 1990;Field, 1981;Resnick, Armstrong, & Carter, 1988;Ross, 1984). According to Field (1981), "the most cost-effective interventions for the ICU neonate may be the education of parents and facilitation of their early interactions with infants" (p. 73).…”
Section: Parental Involvement and Interventionmentioning
confidence: 99%